Use of the fuzzy AHP - MABAC hybrid model in ranking potential locations for preparing laying-up positions - Božanić, Darko I.; Pamučar, Dragan S.; Karović, Samed M. (Vojnotehnički glasnik / Military Technical Courier, 2015)
The paper proposes a hybrid model, FAHP-MABAC. The fuzzyficated Saaty's scale with the AHP method (FAHP) is used for defining the weight coefficients of criteria. The MABAC method is applied in evaluating and ranking the alternatives. This hybrid model is developed in order to support decision making while selecting locations for the preparation of laying-up positions (facilities intended for concealment, protection and maneuvering of military ships).
Keywords: Location selection; Fuzzy AHP; MABAC